Muscle and statins: from toxicity to the nocebo effect. Issue 7 (3rd July 2019) - Pedro-Botet, Juan; Climent, Elisenda; Benaiges, David
ABSTRACT: Introduction : Although statins have a satisfactory safety profile and are well tolerated, many statin-treated patients report muscle symptoms in clinical practice which contribute to drug discontinuation and, consequently, adverse cardiovascular outcomes. Areas covered : This narrative review will cover the definition and prevalence of statin intolerance, the clinical spectrum of statin-associated muscle symptoms (SAMS) with special focus on patients with only mild myalgias, the complexity of statin muscle intolerance diagnosis and provide an overview on the nocebo effect of particular importance for physicians. Expert opinion : Many patients are unable to tolerate statin therapy, with SAMS being the most common cause of statin intolerance. The reported incidence of SAMS was consistently lower in randomized placebo-controlled trials than in observational studies. These results strongly suggested that SAMS were not always due to by the pharmacologic effects of statin therapy. Convincing patients that their muscle symptoms might be due to causes other than statin treatment is sometimes difficult. Furthermore, clinicians should not prematurely discontinue statin therapy before considering other possible causes, including the nocebo effect.